(3GdegPH ef aJGhi GdEeGe YHO Gddg Hf MeRIs - (3eMeO Hf CMeO Hf Ydj Hf CMeO Hf GdhdjO GdbQTi GdYHTeis; (3CHh eMeO YHO Gddg Hf MeRI Hf SdjeGf Hf MeRI GdMSfj Gdjefj,J (B614 (3g` s ((3jhSa Hf Ydi Hf MLGL Hf jhSa Hf MLGL Hf YHO Gddg GdOgdi s)
(3ChdgG (B:s
(3GdMeO ddg MeO GdTGcQjf CeG HYO , aEfi fXQJ aejG LeYg GdbQTi s
(3BNQgG (B:s
(3BNQg ef HGH GdJhHI bhdg (B: (3ai CUMGH GdCShO GdYfSi , hPdc eYdhe def Yde GdBKGQ Je GdcJGH Hef Gddg s
(3cJHJ GdYfGhjjf HGdMeQIs
(3GdfSNI ebGHdI Ydi fSNI eSehYIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3LeYs
Keywords: (3abg GdePGgH GdCNQis